2009 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--4545
|View full text |Cite
|
Sign up to set email alerts
|

“Flipping” The Classroom To Explore Active Learning In A Large Undergraduate Course

Abstract: is currently a PhD Candidate in the Architectural Engineering Department at Penn State. Robert's research focuses on the improvement of team collaboration while leveraging advanced data modeling and visualization technologies for building design and construction. Robert earned his Masters in Architectural Engineering at Penn State, as well as having a background in the construction industry. In addition, Robert has also spend time working with VTT, the Technical Research Center of Finland, as a visiting schola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
1
13

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(101 citation statements)
references
References 0 publications
7
80
1
13
Order By: Relevance
“…A plethora of research has been carried out regarding the implementation and efficacy of flipped classroom approach regarding various sciences (Strayer, 2007;Johnson & Renner, 2012;Szparagowski, 2014;Soliman, 2016). There is scarce research related to the implementation of flipped classroom approach in EFL education, yet there are some studies focusing on English instruction (Snowden, 2012;Baranovic, 2013;Hung, 2015;Webb & Doman, 2016) most of which are conducted in higher education (Strayer, 2007;Pierce & Fox, 2012;Ruddick, 2012;Zappe, Leicht, Messner, Litzinger Lee, 2009;Baranovic, 2013). Ahmed (2016) for example, studied the perceptions of learners on the flipped classroom approach and its impact on their writing achievement at Qassim University.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of research has been carried out regarding the implementation and efficacy of flipped classroom approach regarding various sciences (Strayer, 2007;Johnson & Renner, 2012;Szparagowski, 2014;Soliman, 2016). There is scarce research related to the implementation of flipped classroom approach in EFL education, yet there are some studies focusing on English instruction (Snowden, 2012;Baranovic, 2013;Hung, 2015;Webb & Doman, 2016) most of which are conducted in higher education (Strayer, 2007;Pierce & Fox, 2012;Ruddick, 2012;Zappe, Leicht, Messner, Litzinger Lee, 2009;Baranovic, 2013). Ahmed (2016) for example, studied the perceptions of learners on the flipped classroom approach and its impact on their writing achievement at Qassim University.…”
Section: Introductionmentioning
confidence: 99%
“…Some research suggests that students largely prefer FL to traditional classrooms and report a high level of satisfaction with peer group‐work (Zappe et al. 2009); however, student satisfaction with FL appears to vary widely across studies (O'Flaherty and Phillips 2015).…”
Section: Evidence Of Effectiveness For Bfhmentioning
confidence: 99%
“…In supporting the student-centered learning, several studies (such as Millard, 2012;Baepler, Walker, & Driessen, 2014;Hung,2015;Zappe et al, 2009) reported that FL contributes to active learning through encouraging interaction, collaboration, motivation, and participation. Similarly, other studies (e.g., Day and Foley, 2006;Deslauriers and Wieman, 2011;Hung,2015;Zappe et al, 2009;Kim et al, 2014;Sams & Bergmann, 2013;Wilson, 2013) have reported the benefits of a flipped classroom in supporting students' achievement and involvement. For example, McCallum, Schultz, Sellke, and Spartz 2015, through an exploratory study, they examined the flipped classroom influence on students' performance and achievement.…”
Section: Previous Studies On Flipped Learningmentioning
confidence: 99%